2020
DOI: 10.1186/s12940-020-00631-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial tumors of the central nervous system and air pollution – a nationwide case-control study from Denmark

Abstract: Background: Inconclusive evidence has suggested a possible link between air pollution and central nervous system (CNS) tumors. We investigated a range of air pollutants in relation to types of CNS tumors. Methods: We identified all (n = 21,057) intracranial tumors in brain, meninges and cranial nerves diagnosed in Denmark between 1989 and 2014 and matched controls on age, sex and year of birth. We established personal 10year mean residential outdoor exposure to particulate matter < 2.5 μm (PM 2.5), nitrous oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“… PM 2.5 Boston, New York, Shanghai or Changsha 2010 - 2014 135 first episode schizophrenia patients Interacts with psychosis to reduce hippocampal volume Worthington et al (2020) 8. PM 2.5 Denmark 1989 - 2014 21,057 cases Increased risk factor for CNS tumors Poulsen et al (2020) 9. PM 2.5 Mexico 2007 - 2011 509 mothers Increased the risk of Postpartum depression and neuropsychological dysfunction in mothers Niedzwiecki et al (2020) 10.…”
Section: Impact Of Pm On the Nervous Systemmentioning
confidence: 99%
“… PM 2.5 Boston, New York, Shanghai or Changsha 2010 - 2014 135 first episode schizophrenia patients Interacts with psychosis to reduce hippocampal volume Worthington et al (2020) 8. PM 2.5 Denmark 1989 - 2014 21,057 cases Increased risk factor for CNS tumors Poulsen et al (2020) 9. PM 2.5 Mexico 2007 - 2011 509 mothers Increased the risk of Postpartum depression and neuropsychological dysfunction in mothers Niedzwiecki et al (2020) 10.…”
Section: Impact Of Pm On the Nervous Systemmentioning
confidence: 99%
“…Despite having almost three times more meningioma cases for analysis, there was little evidence of an effect of UFP on risk of meningioma. We are not aware of previous findings on UFP and meningioma but results on air pollution and benign brain tumors were largely null in two large European studies (7,9) and suggestive positive associations were reported only in a small Danish study of nurses (11). Results to date on air pollution and risk of malignant brain cancer are also mixed.…”
Section: Malignantmentioning
confidence: 69%
“…Results to date on air pollution and risk of malignant brain cancer are also mixed. A small increased risk of malignant brain cancer and exposure to PM 2.5 was reported in a majority (10,12,14,15,54) of studies with such data but not all (7,9,16). Although PM 2.5 overall was unrelated to malignant brain cancer risk in the ESCAPE cohort, there was a 67% (95% CI, 0.89-3.14) elevated risk in association with PM 2.5 absorbance, which the authors suggested may be a better proxy for traffic-related particles in the UFP size range (9).…”
Section: Malignantmentioning
confidence: 92%
See 1 more Smart Citation
“…Against this background, we now suspect that poor ventilation indoor, enclosed spaces can lead to the accumulation of bioaerosols (e.g., fungal and bacterial droplets), smoke-related particles (e.g., nitrosamines, cadmium), environmental gases (e.g., ozone, carbon monoxide, nitrogen dioxide), and other particulate matter (e.g., molds and mycotoxins) that when ingested over time causes substantial organismal stress (Figure 4) [39][40][41][42][43][44]. More specifically, epidemiological studies suggest that exposure to PM2.5 can build sufficiently to affect neural circuits driving particular behaviors or pathologies [45][46][47][48]. Although these correlational studies do not reveal causal mechanisms, they are consistent with the tenet that exposure to smoke-related toxins, for instance, can lead to allergic and/or inflammatory diseases of the upper and lower respiratory tract [49,50].…”
Section: Indoor Air Pollutionmentioning
confidence: 99%